Schizolobium parahyba var. Amazonicum Huber ex Ducke. Barneby (paricá) na Amazônia Oriental: caracterização anatômica e modelagem de crescimento - Silva, Marcela Gomes da (2014)
Aiming at the knowledge of the anatomic and physical traits and the growth rate of Schizolobium parahyba var. amazonicum (paricá) trees in Oriental Amazon, we performed studies on the anatomic and physical properties as well as evaluations of growth for this species of native occurrence and homogeneous stands of different ages. For the anatomic studies we followed the COPANT (1974) and IAWA committee (1989) norms in addition to the ABNT NBR 11941 (2003) norms for physical analyses. To evaluate the growth rate, we demarked and measured the growth rings with the LINTAB 6 Scientific measuring system using the Series Analysis and Presentation program. The growth in diameter of the trees was estimated by means of non-linear regression, the volume estimated by adjusted equation and the height by simple regression. In the qualitative anatomic study, there was no difference between native and planted trees. For the homogeneous stands, there was effect between the ages and the municipalities regarding the quantitative anatomic traits and basic density. The wood from planted and native paricá trees presented growth rings marked by the presence of marginal parenchyma band thickening of the fiber wall. The increment of paricá can be determined by means of studying the growth rings.